Analysis of the Circular Letter from the Ditjen Bimas Islam on the Iddah of Wives from the Perspective of Maqāṣid Syarī'ah - Mardhatillah Ali; Abnan Pancasilawati; Mursyid (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
There has been controversy among the community, headmen, and heads of KUA regarding the Circular Letter of the Directorate General of Islamic Guidance Number: P-005/DJ.III/HK.007/10/2021 concerning marriage during the Wife’s Iddah Period, which among its provisions, prohibits the husband's marriage within the iddah period of his wife. The controversy was triggered by the question of whether or not there was iddah for men. This study aims to find out the maqāṣid syarī'ah perspective of Imām al-Syāṭibī on the Circular Letter on Marriage during the wife's iddah. This normative research uses conceptual and historical approaches. The legal analysis uses the concept of maqāṣid syarī'ah Imām al-Syāṭibī both maqāṣid kulliyah and juz'iyyah theories. Results of this Research show that the substance of the Circular Letter is relevant to Imām al-Syāṭibī's maqāṣid syarī'ah principles in that each of its provisions can protect religion, soul, lineage, mind, and property, including the provision prohibiting the husband's marriage during the wife's iddah period. The prohibition is specific to divorce with the status of divorce raj'ī because the maqāṣid is that the existence of iddah in divorce raj'ī serves as a period for both parties (husband and wife) to think clearly about their marriage relationship. Therefore, the Ministry of Religious Affairs, as the formulator of the regulation, needs to disseminate this Circular Letter and especially provide counseling to all KUA so as not to cause different perspectives on this Circular Letter.